If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/6)*(x+4) = 3*x-(4*(2-x))-5 // - 3*x-(4*(2-x))-5
(1/6)*(x+4)+4*(2-x)-(3*x)+5 = 0
(1/6)*(x+4)+4*(2-x)-3*x+5 = 0
1/6*(x+4)+4*(2-x)-3*x+5 = 0
1/6*(x+4)+4*(2-x)-3*x+5 = 0
5-23/6*x-3*x+26/3 = 0
5-41/6*x+26/3 = 0
41/3-41/6*x = 0
41/3-41/6*x = 0
41/3-41/6*x = 0 // - 41/3
-41/6*x = -41/3 // : -41/6
x = -41/3/(-41/6)
x = 2
x = 2
| -114=6(-4+2a)+6a | | -9x-y=-59 | | 58-7x=11x+24 | | 2/5(2x+11)=3(4-3x)+12 | | 2/5x^2+1/5x-2=0 | | -6(1-6r)=138 | | 2/5(2x+11)=3(4x-3x)+12 | | -152=4(4k-6) | | -5n+18+3n=-6 | | n=2-3 | | -107=r+3(7r+1) | | 24x+19x= | | 8(h+3)=7(h-3) | | 25x^5y^3/50x^2y^7 | | 15m+23=-7m+18 | | -9+6v=v-5+6v | | 2X/4+3X/9 | | 2X/4+3X/9+4X/16+5X/25 | | 5a-6b-2a+3b= | | -q-13=2q+5 | | -1+3p=-1p-5p | | 8=4z-3z^2+15 | | x-12=48 | | -5x-2=4-4x | | 5p+6p-y-2p+4y= | | 5*n-7=38 | | 6m-3=-10-6(2-m) | | t+5t+4t-7=17 | | 4-3a=8-4a | | 1x+2=32x-160+80x-70 | | 4x+5/2x+3 | | 5x^2+15x+90=0 |